2010
DOI: 10.1111/j.1440-172x.2010.01897.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking prevalence, attitudes, and perceived smoking prevention and control responsibilities and practices among nurses in Amman, Jordan

Abstract: This study assesses smoking prevalence, attitudes, and perceived patient counselling responsibilities among practicing nurses in Amman, Jordan. It also identifies whether their smoking status or training in counselling patients about smoking is associated with their smoking-related attitudes and counselling practices. Data were collected through a cross-sectional survey of 266 (n = 266) nurses at four public and private hospitals in Amman. Smoking prevalence was 42% for male nurses and 13% for female nurses. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Nonetheless, the gender-specific smoking rates reported in our study are comparable to those previously reported in most cases. For example, current smoking rates in men in these studies have previously been reported to range from 25.4% in Pakistan to 58.0% in Turkey (48.6% in Algeria, 14 37.7% in Egypt, 15~5 0% in Jordan, 16,17 55.2% in Lebanon, 18 31.5% in Morocco, 19 25.4% in Pakistan, 20 56.9% in Syria, 21 58.0% in Turkey 22 and 28.1% in UAE 2 ). In addition, in these national studies, published current smoking rates in women are generally very low and range from 0.5% in Egypt to 44.8% in Lebanon (6.8% in Algeria, 14 0.5% in Egypt, 15 10% in Jordan, 17 44.8% in Lebanon, 18 3.1% in Morocco, 19 3.5% in Pakistan, 20 17.0% in Syria, 21 22% in Turkey 22 and 2.4% in UAE 2 ).…”
Section: Discussionmentioning
confidence: 76%
“…Nonetheless, the gender-specific smoking rates reported in our study are comparable to those previously reported in most cases. For example, current smoking rates in men in these studies have previously been reported to range from 25.4% in Pakistan to 58.0% in Turkey (48.6% in Algeria, 14 37.7% in Egypt, 15~5 0% in Jordan, 16,17 55.2% in Lebanon, 18 31.5% in Morocco, 19 25.4% in Pakistan, 20 56.9% in Syria, 21 58.0% in Turkey 22 and 28.1% in UAE 2 ). In addition, in these national studies, published current smoking rates in women are generally very low and range from 0.5% in Egypt to 44.8% in Lebanon (6.8% in Algeria, 14 0.5% in Egypt, 15 10% in Jordan, 17 44.8% in Lebanon, 18 3.1% in Morocco, 19 3.5% in Pakistan, 20 17.0% in Syria, 21 22% in Turkey 22 and 2.4% in UAE 2 ).…”
Section: Discussionmentioning
confidence: 76%
“…These prevalences are slightly higher than those reported in the overall Jordanian population, listed above. Interestingly, while nurses who participated in this study favored anti-smoking policies, they did not necessarily agree that nurses should council patients about quitting smoking (Merrill, Madanat et al 2010). Of note, a cross-sectional study of 251 physicians from public and private hospitals suggests that the prevalence of smoking among physicians is actually much lower.…”
Section: 9%respectivelymentioning
confidence: 77%
“…11 Other surveillance efforts in the region have been limited to specific populations, such as youth, 12 university students, 13 14 and healthcare professionals. 15 These limitations in the available smoking prevalence data justify the need for detailed national prevalence data on both cigarette and waterpipe smoking among adults in Eastern Mediterranean countries.…”
Section: Introductionmentioning
confidence: 99%